Effect of Flame Retardants and 1% Stabilizer on Burning, Flammability Behaviour, and Thermal Decomposition Properties Via Polypropylene Material Treatmen - Efhema, Mastura A. (Al-Mukhtar Journal of Sciences, 2018)
This study aimed to understand the mechanisn of combining the action of different types of flame netexdents an thermal stability and flammability of Polypropylene polymer (PP). PP Polymer was chosen to be blent in a twin screw extruder with the flame retardants (FR) and an additive, which is a 1% Stabilizer, to investigate Polypropylene's burning moderation and reduce it by studying its burning behavior and thermal decomposition properties. Flammability behaviour tests which is known as LOI were applied in this study. It was found that halogenated flame retardants have a little effect on reducing the rate of gas escape from polymer melt which affects the viscosity, as it was found that APP and FR245 in PP Polymer help in some leftovers of the polymer. All samples with flame retardants and no clay were burnt completely, and the flame spread was reduced and samples were self-extinguished except for the one containing the fire retardants only. All these results were investigated by XRD, Scanning Electron Microscopic (SEM), and Digital images of the charred samples of polymers.